Hubungan Pengetahuan Ibu Hamil Tentang Buku KIA Dengan Pemanfaatan Buku KIA di Wilayah Kerja Puskesmas Torjun Sampang - Jayanti, Nur; Sholihah, Imroatus; Fithriani, Zainun Wahida (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The Maternal Mortality Rate (MMR) in Indonesia is 235/100,000 live births (Kemenkes RI, 2021). Pregnant women's knowledge about the Maternal and Child Health Book (KIA) plays a very important role in supporting the successful use of the KIA book during pregnancy. The purpose of the study is to analyze the relationship between pregnant women's knowledge about KIA books and the use of KIA books in August 2024. The type of analytical research was conducted with cross-sectional and axial sampling techniques with a total of 60 respondents. The majority of respondents had good knowledge as many as 55 people (91.7%), and lack knowledge as many as 5 people (8.3%), using KIA books 54 people (90%) and 6 people (10%) did not use them. Data collection is carried out by distributing questionnaires that have been tested for validity. analysis of Chi Square test data with a significance level of 0.01. The results of the study showed that there was a relationship between mothers' knowledge about KIA books and the use of KIA books, with a value of P=0.000, which showed a value of P<0.001. So, in conclusion, there is a relationship between mothers' knowledge about the KIA Book and the use of the KIA Book in the 2024 Torjun Sampang Health Center Work Area.